Dissociation in families experiencing intimate partner violence. Issue 3 (27th May 2017) - Miller, Alison
ABSTRACT: This paper, using an illustrative case study, presents the hypothesis that cyclical spouse abusers suffer from a dissociative condition (or perhaps a personality disorder in which dissociation is a prominent feature) that results from disorganized attachment. The partner of the spouse abuser tries various unsuccessful strategies to appease her spouse in order to change his behavior. If the relationship lasts for years, she adapts by developing a milder but parallel dissociative process, developing chains of state-dependent memory and resultant ego states for the different phases of the domestic abuse cycle. The children suffer from attachment disruption which can potentially continue the process to the next generation.